GRAMMATICAL PROCESS OF AFFIXES FORMING ASPECT AND MOOD IN TALAUD LANGUAGE - Lalira, James Edward; Pangemanan, Yopie Alex Tomi; Tumuju, Vivi Nansy (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2025)
Languages with extensive morphological systems offer valuable insights into how grammatical meanings are encoded through structural patterns, particularly in lesser-studied agglutinative languages where affixation plays a central role. This study offers an in-depth exploration of the morphological structure of the Talaud language, focusing on the vital role of affixes as indicators of aspect and mood. Understanding this complicated affixation system embraces significant importance in enriching knowledge of linguistic diversity, especially in agglutinative languages that often receive limited scholarly attention. To address this gap, this research examines how morphological marking in Talaud functions not only as a structural mechanism but also as a key determinant of grammatical meaning, enabling a more precise understanding of verbal organization within the language. Through qualitative methodology, functional analysis tools were employed to investigate how even the smallest components within predicates contribute to grammatical meaning. Data collection involved engaging with native speakers through elicitation and comprehensive interviews, enabling access to authentic language use and the significance attributed to affixes in everyday communication. These procedures ensured that the study reflected naturally-occurring linguistic behavior and demonstrated how morphological forms operate within spoken discourse. Research findings reveal that affixes in Talaud consistently maintain sentence meaning, even when certain linguistic features are substituted, illustrating the stability and resilience of the language’s grammatical system, in which morphological processes preserve semantic integrity across structural variations. Identified categories include inceptive, progressive, perfective, and cessative aspects, along with imperative and optative moods, each realized through specific affixation patterns that encode temporal contours and modal attitudes within the predicate. These findings reflect how the affixation system in Austronesian languages governs grammatical meaning independently, ensuring functional stability across syntactic environments and revealing important typological parallels with other agglutinative systems. By elucidating the complexities of aspect and mood in Talaud, this study deepens understanding of its linguistic characteristics and underscores the importance of documenting underrepresented languages, ultimately contributing to a broader and more inclusive perspective on linguistic diversity and highlighting the cultural significance embedded within the Talaud language. Future research is encouraged to explore Talaud across broader discourse contexts and through sociolinguistic, psycholinguistic, and longitudinal perspectives in order to capture the interaction between grammatical structure, language use, and social change.